Uji Daya Hambat Ekstrak Etanol Daun Inai (Lawsonia inermis L.) terhadap Pertumbuhan Staphylococcus aureus - Sasmiati Farach Dita; Lidyawati Lidyawati; Mutiara Sampoerna (Journal of Pharmaceutical and Health Research, 2021)
Henna leaves are often used as traditional medicine, including as an antibacterial. Henna leaves contain several active components including phenols and flavonoids which act as antibacterial. The purpose of this study was to determine antibacterial activity of ethanol extract of henna leaves (Lowsonia inermis L.) against Staphyloccocus aureus. This research was conducted using descriptive method. In this study, ethanol extract of henna leaf was made by maceration method. Ethanol extract of henna leaves was tested against Staphylococcus aureus on Nutrient Agar (NA) medium using well diffusion method with 3 extract concentrations, namely 40%, 50% and 90%, tetracycline as positive control and aquadest as negative control with 3 repetitions each. The results of this study showed that inhibition zone diameter of henna leaves extract at a concentration of 40% was 21.29 mm, at a concentration of 50% was 23.1 mm and at a concentration of 90% was 24.4 mm, positive control was 27.93 mm and negative control did not show inhibition zone. The inhibition zone for all concentrations belongs to strong inhibition category.